Khilek Curry and the Full-Moon Medicine: Ethnobotanical notes on the Senna siamea ritual of Nakhon Chum, Thailand - Panyadee, Prateep; Tipayanon, Anusorn (Ethnobotany Research and Applications, 2026)
Background: Senna siamea (khilek) is a common bitter vegetable and medicinal plant in mainland Southeast Asia. In Nakhon Chum, Kamphaeng Phet Province, a unique full-moon ritual known as Pli Ya transforms the local khilek curry (kaeng khilek) into a medicinal dish believed to protect health and bring good fortune. Methods: Ethnobotanical data were collected through semi-structured interviews with community elders, direct observation of the 2025 Pli Ya ritual, and photographic documentation. Field notes were supported by informal discussions with local cooks and ritual participants. Results: Households prepare kaeng khilek using young buds gathered before sunrise on the full moon of the twelfth lunar month. The curry, shared within the community, symbolizes both food and medicine, reflecting beliefs that moonlight enhances the plant’s healing properties. Conclusions: The Pli Ya tradition of Nakhon Chum illustrates the fusion of ecology, belief, and healing in Thai ethnobotany. It exemplifies how ritual timing and shared food practices sustain cultural memory and the concept of “food as medicine.” Keywords: Senna siamea, khilek, full-moon ritual, ethnobotany, Thailand